Produzioni e insediamenti nella Sicilia orientale in età romana e tardo antica: Nuovi dati dalle ricerche nell’area archeologica di Santa Venera al Pozzo (Catania) - Malfitana, Daniele; Cacciaguerra, Giuseppe; Mazzaglia, Antonino; Leucci, Giovanni; De Giorgi, Lara (Rei Cretariae Romanae Fautorum Acta, 2022)
The IBAM-CNR team has recently conducted a comprehensive research program aimed at studying the dynamics of production, distribution and consumption of roman and byzantine pottery in eastern Sicily, in particular around the ancient city of Catania. The research was also focused on the archaeological site of Santa Venera al Pozzo, near Catania, placed along the roman Via Pompeia. During last decade, three pottery kilns and many wasters were identified and dated between the 4th and 5th century AD. Recently, archaeometric analysis have established that the kilns produced the Mid Roman 1A–B amphorae, in addition to common pottery and roofing tiles. Between 2015 and 2016, the IBAM team conducted an extensive geophysical research program (Ground Penetrating Radar, Electrical Resistivity Tomography and Magnetometry) in order to identify and define the late roman workshop area. The surveys have led to the possible identification of other four kilns in the same area. It was, therefore, a very important production center which made a large volume of ceramics and amphorae for the export of Etna wine. It supplied a wide area of eastern Sicily and carried amphorae around the Mediterranean and Europe.